Clinical Practice Guideline for Physical Therapy Assessment and Treatment in Patients With Nonspecific Neck Pain. Issue 3 (4th December 2017) - Bier, Jasper D; Scholten-Peeters, Wendy G.M; Staal, J Bart; Pool, Jan; van Tulder, Maurits W; Beekman, Emmylou; Knoop, Jesper; Meerhoff, Guus; Verhagen, Arianne P
Abstract: The Royal Dutch Society for Physical Therapy (KNGF) issued a clinical practice guideline for physical therapists that addresses the assessment and treatment of patients with nonspecific neck pain, including cervical radiculopathy, in Dutch primary care. Recommendations were based on a review of published systematic reviews. During the intake, the patient is screened for serious pathologies and corresponding patterns. Patients with cervical radiculopathy can be included or excluded through corresponding signs and symptoms and possibly diagnostic tests (Spurling test, traction/distraction test, and Upper Limb Tension Test). History taking is done to gather information about patients' limitations, course of pain, and prognostic factors (eg, coping style) and answers to health-related questions. In case of a normal recovery (treatment profile A), management should be hands-off, and patients should receive advice from the physical therapist and possibly some simple exercises to supplement "acting as usual." In case of a delayed/deviant recovery (treatment profile B), the physical therapist is advised to use, in addition to the recommendations for treatment profile A, forms of mobilization and/or manipulation in combination with exercise therapy. Other interventions may also be considered. The physical therapist is advised not to use dry needling, low-level laser, electrotherapy, ultrasound, traction, and/or a cervical collar. In case of a delayed/deviant recovery with clear and/or dominant psychosocial prognostic factors (treatment profile C), these factors should first be addressed by the physical therapist, when possible, or the patient should be referred to a specialist, when necessary. In case of neck pain grade III (treatment profile D), the therapy resembles that for profile B, but the use of a cervical collar for pain reduction may be considered. The advice is to use it sparingly: only for a short period per day and only for a few weeks.